An electron rich indaceno [2, 1-b:6, 5-b′] dithiophene derivative as a high intramolecular charge transfer material in dye sensitized solar cells. (27th January 2021) - Barłóg, Maciej; Yavuz, Cagdas; Ali, Abdulrahman K.; Kandemir, Zafer; Comí, Marc; Bazzi, Hassan S.; Al-Hashimi, Mohammed; Erten-Ela, Sule
Abstract : The synthesis, characterisation and photovoltaic performance of an indacenodithiophene (IDT)-based organic dye in DSSCs has been presented. Abstract : The synthesis, characterisation and photovoltaic performance of an indacenodithiophene (IDT)-based organic dye in DSSCs has been presented. The dye was designed with a novel A–D–A system, which combines the advantages of a large, π-extended donor core, flanked with double acceptor/anchoring groups. The studies presented herein illustrate the utility of the IDT core as an efficient energy-level mediator, and fluorescence resonance energy-transfer module operating via intramolecular charge transfer (ITC). In contrast to the current dyes used for DSCCs, the excitation in the IDT moiety occurs symmetrically along the long axis of the molecule, representing a new pathway of development of DSSCs. This compact system when fabricated into a metal free dye sensitized solar cell achieves promising power conversion efficiency of up to 4.2%, with a high short-circuit current density ( J sc ) of 11.69 mA cm −2 and open-circuit voltage ( V oc ) of 0.6 V and fill factor (FF) of 0.6 under AM 1.5 irradiation (100 mW cm 2 ).